Iris from Iridectomy Used as Spacer underneath the Scleral Flap: The Iridenflip Trabeculectomy Technique - Veva De Groot; Liselotte Aerts; Stefan Kiekens; Tanja Coeckelbergh; Marie-José Tassignon (Journal of Ophthalmology)
Purpose. We describe a modified trabeculectomy technique in which the iris is used to prevent fibrosis of the scleral flap. Material and Methods. A retrospective case series of patients with medically uncontrolled open angle glaucoma underwent trabeculectomy. Instead of performing a classical iridectomy, the iris was used as spacer underneath the scleral flap. Postoperative management was identical to classical trabeculectomy, with suture removal and needling if necessary. Five of the patients underwent simultaneous phacoemulsification through a separate temporal corneal incision. Patients should have two-year follow-up. Results. Data of ten patients were analysed, two had a previous failed trabeculectomy, two had LTP, and one had a corneal transplantation. In 3 patients MMC 0,1 mg/mL was used. After one and two years mean IOP was, respectively, 13,1 and 12,1 mmHg. IOP ≤ 16 mmHg was reached in 90% of patients without pressure lowering medication. No major complications were seen; no abnormal inflammatory reaction and no deformation or dislocation of the pupil occurred. Conclusion. By using the iris from the iridectomy as spacer under the scleral flap, fibrosis of the scleral flap is no longer possible. This iridenflip trabeculectomy technique gives an excellent complete success rate (IOP ≤ 16 mmHg) of 90%. A larger study is currently being done.